Catching the chloride: searching for non-Hofmeister selectivity behavior in systematically varied polyamide macrocyclic receptors. Issue 28 (4th July 2017) - Dabrowa, Kajetan; Ulatowski, Filip; Lichosyt, Dawid; Jurczak, Janusz
Abstract : Searching for regularities in the large set of structurally diverse macrocyclic probes allowed us to determine the structural requirements for the selective recognition of chloride over more basic anions such as H2 PO4 − or RCO2 − by a putative anion receptor. Abstract : The binding selectivity of structurally simple anion receptors is governed by the Hofmeister series (SO4 2− > HPO4 2− > carboxylates ∼ H2 PO4 − > HCO3 − > Cl − ), and exceptions to this rule are rare and require utilization of structurally sophisticated receptors. In this paper we examined a set of 48 structurally diverse anion receptors, barely one fourth of which exhibit selectivity for chloride over more basic dihydrogen phosphate (H2 PO4 − ) or carboxylates (MeCO2 − and PhCO2 − ). Searching for regularities in the properties of these mainly macrocyclic-derived receptors across quite systematic changes in structure, combined with analysis of multiple crystal structures, allowed us to identify the crucial structural features that are likely required for the occurrence of the phenomenon of selective chloride binding. Examination of a subset of other 'case study' receptors reported in the literature as being particularly chloride-selective served as a confirmation of our hypotheses. As such, our findings are valid for all artificial receptors with exceptional selectivity for chloride, as well as for natural chloride channel proteins (ClC).